Dual-plane ultrasonic tomography simulation using cross-correlation technique for velocity measurement in two-phase liquid/gas flow / N. M. Nor Ayob ...[et al.] - Nor Ayob, N. M.; Fazalul Rahiman,, M. H.; Zakaria, Z.; Yaacob, S.; Abdul Rahim, R. (UiTM Press, 2011)
Combining Ultrasonic Transmission Tomography ,UTT with the cross-correlation flow measurement technique can provide more information on the flow than usual. A simulated dual-plane UTT system for use on laboratory and plant-scale process equipment has been developed on the basis of this idea. This paper focuses on the correlator used to cross-correlate the tomogram images between the downstream and upstream plane of the simulated dual-plane ultrasonic transmission tomography system. This paper proposed the use of 2D correlation coefficient for the correlator and the result of its usage is discussed. The principle of measurement of the local gas velocity distribution in a bubbly gas/liquid pipe flow which is based on cross-correlation of two plane images is also described. Initial experimental results illustrate the feasibility of the method presented in this paper.